The assesment of lipid peroxidation processes disturbances in animals` lungs in condition of experimental parodontitis development - Solvar, Zoryana (Journal of Education, Health and Sport, 2022)
An imbalance between generation of free radicals and antioxidant defence leads to an oxidative stress Pulmonary damage caused by oxygen toxicity occurs due to the generation of reactive oxygen species and subsequent formation of more potent oxidants in experimental peridontitis development. Furthermore, the reactive oxygen species content may be a useful and practical parameter for evaluating periodontal disease activity.